THE MEDIATING ROLE OF ENTREPRENEURIAL SELF-EFFICACY IN THE EFFECTS OF NEED FOR ACHIEVEMENT AND SELF-CREATIVITY ON ENTREPRENEURIAL INTENTION AMONG WOMEN ENTREPRENEURS IN JAKARTA - Vallerine, Jessyca; Handoyo, Sarwo Edy (International Journal of Application on Economics and Business, 2023)
The purpose of this study is to analyze women entrepreneurship in Indonesia particularly to examine the need for achievement, creativity and entrepreneurial self-efficacy on entrepreneurial intentions, and the mediation role of entrepreneurial self-efficacy on both relationships. This study uses a quantitative approach and online survey in the data collection process. The population in this study are employees who work in the culinary field in Jakarta city. The sample in this study was taken using a purposive sampling technique. We obtained 126 respondents and analyzed by using partial least square structural equation modeling (PLS-SEM) WarpPls 7.0. The results showed that the need for achievement and entrepreneurial self-efficacy had a positive and significant effect on entrepreneurial intentions, and also entrepreneurial self-efficacy mediates the impact of creativity on entrepreneurial intentions. This study did not find a significant effect of creativity on entrepreneurial intentions, and entrepreneurial self-efficacy did not mediate the impact of need for achievement on entrepreneurial intentions.